Failed Spinal Anesthesia Status in Cesarean Section; A Report from a Teaching - Fatemeh Hosseinzadeh; Arezoo Mansouri; Soheil Soltanipour; Zahra Rafiei Sorouri; Gelareh Biazar (Caspian Journal of Neurological Sciences)
Background: The incidence of failed spinal anesthesia (FSA) for cesarean section (CS) varies widely among hospitals. Several risk factors have been proposed, but their predictive value remains unknown. Objectives: The main objective of this prospective study was to evaluate the incidence of FSA for cesarean deliveries in an academic obstetric hospital, and the secondary objective was to determine its predictive factors. Materials & Methods: This analytic descriptive study was performed in a referral obstetric hospital affiliated with Guilan University of Medical Sciences from May 2024 to August 2024. The study enrolled women who underwent elective and emergency CS under spinal anesthesia, classification of The American Society of Anesthesiologists (ASA-I and ASA-II). A checklist containing women’s demographic data, surgery characteristics, and FSA rate was completed. Results: A total of 241 women with a Mean±SD age of 29.54±6.64 years and body mass index (BMI) of 27.98±3.16 kg/m2 participated. About 46 women (19.1%) underwent emergency CS and 195(80.9%) elective. Overall, the incidence of FSA was 7.9%. Of 19 FSA cases, 12(5%) received supplemental analgesia or sedation; in 5(2.1%) cases, the procedure was repeated, and only two cases underwent general anesthesia (GA). The most important predictive factors of FSA were BMI (P=0.003), emergency CS (P=0.0001), level of residency (P=0.037), bloody cerebrospinal fluid (P=0.0001), the number of attempts (P=0.0001), and ASA class (P=0.035). Conclusion: In 7.9% of women, spinal anesthesia did not provide appropriate conditions for CS. Significant predictors included higher BMI, emergency surgeries, level of anesthesia residency, bloody CSF, the number of attempts, and ASA class.